Kiai, Religious Authority, and Dynamics of Ngumbah Keris Tradition in Java, Indonesia - Faline Izza Nisa`u; Ahmad Arif Widianto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The ngumbah keris tradition is recognized as a practice aimed at warding off bad luck through a series of specific rituals that incorporate mantras and offerings. This study explores the responses of kiai langgar to the ngumbah keris ritual using ethnographic methodology. Data were collected through purposive sampling, in-depth interviews, participatory observations, and documentation. The analysis adhered to Miles and Huberman's interactive model, which encompasses data reduction, data display, and conclusion drawing, supplemented by triangulation to ensure both validity and reliability. Max Weber's theory of charismatic authority provided the theoretical framework for this study, which is crucial for understanding how kiai langgar exercise their authority to mediate between traditional practices and religious principles. This framework highlights a dualistic response: kiai langgar aligned with Nahdlatul Ulama view the ritual as a means of seeking divine blessings, provided it is in accordance with Islamic teachings. In contrast, kiai langgar associated with Muhammadiyah classify the ritual as bid'ah (innovation) and superstition. The findings indicate that the negotiation of religious and cultural values is significantly shaped by the charismatic authority of the kiai langgar, influencing community perceptions and practices. This study deepens the understanding of the complex interplay between traditional rituals and Islamic teachings within rural Javanese communities, underscoring the role of kiai langgar as cultural brokers and agents of social change.